Pay-per-click (PPC) advertising (Henry Stewart Talks, 2025)
PPC basics, Keyword bidding & auctions, Ad rank factors, PPC targeting & measurement, PPC challenges & optimisation, Automation in PPC, Ongoing performance tracking